2020
DOI: 10.1093/conphys/coaa108
|View full text |Cite
|
Sign up to set email alerts
|

Thermal tolerance and fish heart integrity: fatty acids profiles as predictors of species resilience

Abstract: The cardiovascular system is a major limiting system in thermal adaptation, but the exact physiological mechanisms underlying responses to thermal stress are still not completely understood. Recent studies have uncovered the possible role of reactive oxygen species production rates of heart mitochondria in determining species’ upper thermal limits. The present study examines the relationship between individual response to a thermal challenge test (CTmax), susceptibility to peroxidation of membrane lipids, hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Given the high degree to which cells can regulate membrane performance and the many other functions for lipids in the body, it is not surprising that only approximately 20-30% of the variation in f Hmax could be explained by fatty acid composition. Christen et al [59] found significant negative linear relationships between thermal limits (time to CT max ) and omega-3 fatty acid composition in Salvelinus alpinus, S. fontinalis, and their hybrids. Here, there were some significant correlations between specific fatty acids and cardiac thermal limits, although there was no significant linear regression found between overall DBI and cardiac thermal limits.…”
Section: (B) Thermal Acclimation Rate Did Not Change With Dietmentioning
confidence: 99%
“…Given the high degree to which cells can regulate membrane performance and the many other functions for lipids in the body, it is not surprising that only approximately 20-30% of the variation in f Hmax could be explained by fatty acid composition. Christen et al [59] found significant negative linear relationships between thermal limits (time to CT max ) and omega-3 fatty acid composition in Salvelinus alpinus, S. fontinalis, and their hybrids. Here, there were some significant correlations between specific fatty acids and cardiac thermal limits, although there was no significant linear regression found between overall DBI and cardiac thermal limits.…”
Section: (B) Thermal Acclimation Rate Did Not Change With Dietmentioning
confidence: 99%
“…Christen et al . [59] found significant negative linear relationships between thermal limits (time to CT max ) and omega-3 fatty acid composition in Salvelinus alpinus, Salvelinus fontinalis , and their hybrids. Here, there were some significant correlations between specific fatty acids and cardiac thermal limits, although there was no significant linear regression found between overall DBI and cardiac thermal limits.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high degree to which cells can regulate membrane performance and the many other functions for lipids in the body, it is not surprising that only ~20-30% of the variation in fHmax could be explained by fatty acid composition. Christen et al [59] found significant negative linear relationships between thermal limits (time to CTmax) and omega-3 fatty acid composition in Salvelinus alpinus, Salvelinus fontinalis, and their hybrids. Here, there were some significant correlations between specific fatty acids and cardiac thermal limits, although there was no significant linear regression found between overall DBI and cardiac thermal limits.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, there is no consensus about the OCLTT hypothesis (e.g., [ 65 , 66 ]) including in salmon, as other studies have shown that the aerobic scope of Atlantic salmon (~450 g fish) remains the same across different temperatures (13, 18, 23 °C) [ 61 ]. Thus, thermal tolerance limits of fish could be oxygen-independent [ 67 ] and be related to other mechanisms, namely loss of macromolecular integrity (e.g., [ 68 ]), dysregulation of sarcolemmal ion regulation (altering ventricular excitation, e.g., [ 69 ]) and disruption of biological membranes and antioxidant capacity (e.g., [ 70 ], and see [ 71 ] for a brief discussion). Other authors have also shown that thermal tolerance limits are modulated by heat-induced neural dysfunction associated with limited oxygen availability [ 72 ].…”
Section: Adult Atlantic Salmon Thermal Tolerance and Physiological Responses To Heat Stressmentioning
confidence: 99%